PENGARUH PEMBERIAN REWARD DALAM PEMBELAJARAN SOSIOLOGI TERHADAP MOTIVASI INTRINSIK SISWA KELAS XI IPS MATLA’UL ANWAR - Ariansyah, Jono; Rustiyarso, Rustiyarso; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the effect of reward on the intrinsic motivation of students in the sociology subjects of class XI Matla'ul Anwar. The research method used is using quantitative research with a form of correlation study research. The study population was 60 students. The data source of this study was the students who were sampled using the XI class sampling technique as many as 53 students and the data was the student questionnaire answer sheet about the students' intrinsic reward and motivation. The results obtained showed that the reward for the intrinsic motivation of students was in the high category of 68.8 and 54.8%. The results of hypothesis testing show that there is a positive and significant effect between reward on intrinsic motivation and the price of r count (0.357)> r table (0.266). While the significance value (0.009) <significance level (0.05). The regression equation Y = 17.444 + 0.540 X shows that the reward increases by one, then intrinsic motivation increases by 0.128. The determinant value of adjusted R2 = 0.772, which means that the contribution of the influence of reward on the intrinsic motivation of students is very low 12.8% and 77.2 is determined by other factors that are not meticulous researchers Â Keywords: Giving Reward, learning Sociology, Intrinsic Motivation of Students